Design and development of a fully automated consumer-based wireless communication system for fruit grading - Yit W.B.; Mustafa N.B.A.; Ali Z.; Ahmed S.K.; Sharrif Z.A.Md. (2023)
As a smart consumer, there is always a need for us to identify the quality of the goods we want to buy, such as trying to choose the better mango amongst the others in a fruit market. With the popularity of the mobile phone and the maturity in wireless messaging technology, it is no more a dream for us to get the information we want anywhere, anytime. This paper proposes a new mobile data service that includes signal processing service via MMS (Multimedia Messaging Service) and SMS (Short Messaging Service). This paper discusses the study, design, construction and analysis of a fully automated consumer-based prototype wireless system which interconnects signal processing tools with consumers using MMS and SMS technology. The system with signal processing application processes the information sent by the consumer using MMS. Then it sends back the grading result to the consumer using SMS. 2009 IEEE.